A novel system for drying of agro-industrial acerola (Malpighia emarginata D. C.) waste for use as bioactive compound source. (March 2019) - Silva, P.B.; Duarte, C.R.; Barrozo, M.A.S.
Abstract: The industrial processing of acerola generates a large amount of waste that is usually discarded or underutilized, causing losses of raw material and energy, as well as environmental impact. As these agro-industrial residues are rich in antioxidant compounds, they can be better used. In this work the drying of acerola residues in a novel device (roto-aerated dryer) was investigated. The high moisture content of this residue demanded multiple drying stages to achieve the suitable final moisture. The effects of the number of drying stages and operating conditions on product quality and drying performance were analyzed. The bioactive compounds analyzed were: phenolic, flavonoid, ascorbic acid and citric acid. The results shown that the new drying system proved to be a good alternative for dehydration of acerola residues, due to the drying performance and the good quality of the product after drying. Highlights: The industrial processing of acerola generates a large volume of waste that are underutilized. A new dehydration system was proposed for the best use of these fruit residues. Conditions with high moisture removal and short residence times were identified. The product quality has been analyzed considering the content of bioactive compounds. Conditions with high product quality levels were also identified.